2011
DOI: 10.1111/j.1447-0594.2010.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional factors in activities of daily living that predict falls in community‐dwelling older women

Maki Aoyama,
Yusuke Suzuki,
Joji Onishi
et al.

Abstract: The results confirmed that the sub-item in the Motor Fitness Scale has a possibility of being a significant predictor of falls in older women, and therefore might prove useful in considering specific rehabilitation program on falls prevention as well as screening this population at risk of falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 47 publications
5
49
0
2
Order By: Relevance
“…In a crosssectional study, Fukutomi et al [9] showed that at-risk groups in all KCL categories exhibited lower ADLs, lower subjective quality of life scores, and higher scores on a geriatric depression scale. The results of our multivariate analyses are consistent with previous studies reporting that age [19], lower back pain [25], falls [17], previous fractures [26], and cerebral stroke [27], are all factors associated with poorer scores in the KCL lifestyle category.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In a crosssectional study, Fukutomi et al [9] showed that at-risk groups in all KCL categories exhibited lower ADLs, lower subjective quality of life scores, and higher scores on a geriatric depression scale. The results of our multivariate analyses are consistent with previous studies reporting that age [19], lower back pain [25], falls [17], previous fractures [26], and cerebral stroke [27], are all factors associated with poorer scores in the KCL lifestyle category.…”
Section: Discussionsupporting
confidence: 82%
“…HGS was also associated with the KCL physical strength category. Muscle strength of handgrip was associated with the TUG, functional balance measured by the Berg Balance Scale score, and walking speed [17][18][19]. The above results may have been obtained for these reasons.…”
Section: Discussionmentioning
confidence: 88%
“…Elderly persons commonly fall (Kojima et al 2011;Aoyama et al 2011), in part because they can only lift their toes a maximum of 1 cm from the floor when they walk (Chiba et al 2005). Because Japanese floor mats can vary by 5 mm in height, the elderly can easily trip and fall at a junction between two mats.…”
Section: How To Prevent the Need For Nursing Carementioning
confidence: 99%
“…It is not clear, however, what amount or intensity of physical activity/exercise is needed to reduce the occurrence of falls and related injuries or how physical activity interacts with other risk factors for falls. The successful completion of daily tasks (without falling) is dependent on intrinsic factors such as age, health, physical fitness and fear of falling, and also on extrinsic factors such as the demands of each task and environmental hazards [4,20,21]. Thus the main purpose of this study was to analyse the role of physical activity in falls and related injuries in community-dwelling adults aged over 50 years, adjusting for these intrinsic and extrinsic risk factors.…”
Section: Introductionmentioning
confidence: 99%